2002
DOI: 10.1002/cyto.10114
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric detection of activated mouse integrin αIIbβ3 with a novel monoclonal antibody

Abstract: Background Integrin αIIbβ3 mediates platelet adhesion and aggregation and plays a crucial role in thrombosis and hemostasis. αIIbβ3 is expressed in a low affinity state on resting platelets. Upon platelet activation, αIIbβ3 shifts to a high affinity conformation that efficiently binds its ligands. On human platelets, the high affinity conformation of αIIbβ3 is detected by the monoclonal antibody (mAb), PAC‐1. However, a reagent with binding specificity to high affinity mouse αIIbβ3 has not been described so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 18 publications
7
117
1
1
Order By: Relevance
“…In parallel, activation of the main platelet integrin, ␣ IIb ␤ 3 , was assessed. 35 Surprisingly, and in contrast to studies in other cell types, we found that P-selectin expression was not decreased but markedly increased in Cdc42 Ϫ/Ϫ compared with wild-type platelets in response to all tested strong agonists ( Figure 4A; bottom panel). In line with this, release of PF4, a protein specifically stored in platelet ␣ granules, was also moderately but significantly increased in Cdc42 Ϫ/Ϫ platelets upon activation compared with the control (Figure 4B).…”
Section: Increased Secretion In Cdc42 ؊/؊ Plateletscontrasting
confidence: 49%
“…In parallel, activation of the main platelet integrin, ␣ IIb ␤ 3 , was assessed. 35 Surprisingly, and in contrast to studies in other cell types, we found that P-selectin expression was not decreased but markedly increased in Cdc42 Ϫ/Ϫ compared with wild-type platelets in response to all tested strong agonists ( Figure 4A; bottom panel). In line with this, release of PF4, a protein specifically stored in platelet ␣ granules, was also moderately but significantly increased in Cdc42 Ϫ/Ϫ platelets upon activation compared with the control (Figure 4B).…”
Section: Increased Secretion In Cdc42 ؊/؊ Plateletscontrasting
confidence: 49%
“…We used the JON/A antibody to study the agonist-induced signaling. This antibody reacts selectively with the activated conformer of αIIbβ3 (Bergmeier et al, 2002). We did not observe any significant differences between wild-type and Fyn -/-mice with respect to JON/A binding that was induced by thrombin or two different doses of ADP (Table 1).…”
Section: Characterization Of Fyn -/-Micementioning
confidence: 68%
“…Moreover, a strong reduction in platelet-mediated adhesion of B16 melanoma cells was achieved after preincubation of murine platelets with a blocking anti-CD61 (␤3 integrin) mAb or an anti-GPIIb/ IIIa Ab (JON/A) (Fig. 3, B and C) (37). To exclude that reduced melanoma cell adhesion was caused by a reduction in the number of present platelets after incubation with RGD or antiGPIIb/IIIa Ab, the number of platelets in the well was analyzed and showed no difference between control and inhibitory protein (supplemental Fig.…”
Section: Resultsmentioning
confidence: 98%